PERANCANGAN PILAR PORTAL STRUKTUR JEMBATAN CIKERUH RUAS JALAN CICALUNG-SP.SINDANG PT.DELIMA DJAYA INTILAND - Amarudin, Amarudin; Kholiq, Abdul (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The Cikeruh Bridge is a bridge that crosses the Cikeruh river with a river width of 65 meters, on the west it is a steep slope of 900 in the east there are landslides with a depth of 11 meters where there are rocks of varying sizes. So the construction of the pillar as a support for the superstructure must be very carefully calculated so that it is able to transfer the weight of the upper structure to the ground. The type of pillar chosen at the location of the Cikeruh bridge is a portal pillar with a different construction between one pillar and another, adjusted to the contour of the land and the flow of the river. The structure of the bridge itself is planned for a composite bridge type with steel girders (Fy = 355 MPa) and a concrete plate (F'c = 250 MPa), with a structure under a steel pile foundation. and Pier head work 2. The main material used in the construction of cikeruh bridge pillars is f'c = 250 quality concrete, the reinforcement used is screw D-25 iron, threaded D-16 and threaded D-13.